2022
DOI: 10.1055/s-0042-1743525
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Hemorrhage following Spinal Surgery: A Systematic Review of a Rare Complication

Abstract: Introduction Intracranial hemorrhage (ICH) is a potentially severe complication of spinal surgeries. The occurrence of such complications causes deterioration of the patient's clinical status and delayed discharge from the hospital. Although no specific etiological factors were identified for this complication, but multiple risk factors might play role in its development, they include the use of anticoagulants, presence of uncontrolled hypertension, and perioperative patient positioning. Aim A system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 25 publications
(40 reference statements)
0
10
0
Order By: Relevance
“…In 2011, Abd‐Elsayed et al reported that also facial swelling due to the prone position in spinal surgery might lead to abducens nerve ischemia 6 . Al‐Saadi et al published a rare complication of intracranial hemorrhage after accidental durotomy following spinal surgery 7 . But due to the follow‐up MRI scans, no intracranial hemorrhage could be observed in our patient, so that the cause of the nerve palsy had to be evaluated otherwise.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In 2011, Abd‐Elsayed et al reported that also facial swelling due to the prone position in spinal surgery might lead to abducens nerve ischemia 6 . Al‐Saadi et al published a rare complication of intracranial hemorrhage after accidental durotomy following spinal surgery 7 . But due to the follow‐up MRI scans, no intracranial hemorrhage could be observed in our patient, so that the cause of the nerve palsy had to be evaluated otherwise.…”
Section: Discussionmentioning
confidence: 71%
“…6 Al-Saadi et al published a rare complication of intracranial hemorrhage after accidental durotomy following spinal surgery. 7 But due to the follow-up MRI scans, no intracranial hemorrhage could be observed in our patient, so that the cause of the nerve palsy had to be evaluated otherwise. To sum up, 6th nerve palsy can be caused due to alterations of intracranial pressure or mechanic injury.…”
Section: Discussionmentioning
confidence: 74%
“…The incidence of intracranial hemorrhage after spinal surgery in our study was 0.025% (6/24472), which was extremely low. An Egyptian study demonstrated that the incidence of intracranial hemorrhage was 0.066% (8/12185)[ 1 ]. A six-year retrospective study in Japan showed that 53 of 167106 (0.03%) patients developed hemorrhagic stroke after spinal surgery[ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intracranial hemorrhage after spinal surgery is a rare but disastrous postoperative complication, with poor clinical prognosis[ 1 ]. It has a heavy economic and social burden but lacks clinical data in these areas.…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative intracranial hemorrhage (PIH) is a fairly rare but horrible complication that can follow endoscopic spinal surgery [ 1 , 2 , 3 ]. The incidence of PIH occurring after any spinal surgery is about 0.12% to 0.74%, as reported in the literature so far [ 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%